Orientalistinis pėdsakas misionieriaus Kristupo Lokio gyvenime ir publikacijose - Kaunas, Domas (Knygotyra, 2003)
An important source for the studies of orientalist topics is Lithuanian press of the Lithuanian part of Prussia – Lithuania Minor. It was embedded by Lithuanian missionaries who worked in the German Evangelist Lutheran missions in Africa and South-East Asia. The first one was Dovydas Didlaukis (1836–1897) who travelled to India in 1863. He worked in the missions of Bengal: Govindpur, Gosnerpur, Ranchi and others. Before the First World War, eight Lithuanians (some of them together with their families) worked in the missions in India and China. All of them maintained relations with their homeland and relatives. Some of these missionaries were gifted connoisseurs of exotic Oriental languages, creative, sensitive, and devoted personalities. From their publications in Lithuanian press of Lithuania Minor, Lithuanians of the 19th century were well acquainted with the spiritual world of the indigenous inhabitants of India, China, North and South Africa, as well as with the exotic nature of these countries. A book also played an important role in information and communication. Only during the first decade of the 20th century, Lithuanian missionaries translated into their native language and published more than thirty popular books of different size and contents. Kristupas Lokys (1860–1921) was very active in the press. He spent a quarter of a century in Bengal and perceived his duty much wider than just christianisation of the indigenous population. Lokys has established a hospital, his constant concern was to provide food and medicine, he taught agricultural methods to Indians, constructed a dam on the river to hold the water and used it for irrigation and watering cattle. The missionary won great respect of Indians, as well as a meaningful and memorable conservation of his name for his devotion and commitment. The river dam was reconstructed and modernized many times. It is standing until now and is named after Kristupas Lokys. His wife was a teacher at local schools. She taught handcraft to Indian children. The publications by Lokys in the press of his homeland reflected the everyday life in the mission, the spiritual and material life of the local population. They allowed readers to perceive the differences of civilisations and cultures and the work among "pagans" (as all members of local beliefs were called) for the sake of "christianisation". These publications also revealed the relations between missionaries and locals, the conditions, which were essential for the survival of newcomers from Europe, the impact of a complex environment and unusual climate. The author persistently publicised the spiritual and social injustice that English colonisation inflicted on India. The work of a missionary was a way and possibility of self-expression for Lokys. It formed his mind and stimulated creativity. The oriental experience had a clear influence on his civil and spiritual world-view, underpinned critical evaluation of the situation and causes of enslaved nations, determined the patriotic choice. India became the source of originality in his works. After return to the homeland (1914), Lokys became an active member of Lithuanian national and political movement.